Prevalence of Rheumatoid Arthritis and DMARDs Usage in Indian Population: A Cross-Sectional Study (Asian Journal of Pharmaceutics (AJP), 2021)
Background: Rheumatoid arthritis (RA) is an autoimmune disorder characterized by symmetric and erosivesynovitis with extra-articular involvement in some cases. RA prevalence in India is 0.75%. The study is toestimate the prevalence of RA in the South Indian population and to determine the demographic characteristicssuch as gender, age, geographical locality, and usage of antirheumatic drugs. Methodology: This prospectivecross-sectional study was conducted in 600 patients of both male and female at advance rheumatology center. Thepatients were selected based on inclusion and exclusion criteria. Patients who are suspected and diagnosed newlywith RA, patients who are already with RA attending the rheumatoid center and are on therapy, and patients ageequal to and above 16 years either gender are included in the study. Patients with other arthritic and immunologicproblems such as osteoarthritis, psoriatic arthritis, systemic lupus erythematosus, spondylosis, and osteoporosiswere excluded from the study and patient’s age below 16 years are excluded from the study. Results: Among600 patients presented to advance rheumatology center, 174 patients are identified with classical symptoms of RA,in those female and male patients are 132 and 42, respectively. The mean age of total patients is 45.51 ± 12.09. Theestimated prevalence was found to be 0.29 or 29% (95% confidence interval is 0.25–0.33). Disease-modifyingantirheumatic drugs (36.9%) are mostly prescribed. Conclusion: This study witnessed a rise in the prevalence ofRA in South Indian population which gives alarming signals to the health authority and policymakers to increasethe awareness on RA in India.